The Birth of the Free Church Tradition - Maclear, James Fulton (Church history, 1957)
The free church form which much of British and American Protestantism has assumed stems primarily from the shaping of Nonconformity in seventeenth-century England. Yet the uniqueness and significance of this origin have not always been appreciated. These English and American churches have a basis distinct from that of the free churches which arose on the Continent in the nineteenth century. For unlike the latter, the free churches of Nonconformity developed within the fabric of Christian state and society and not out of any fundamental ideological conflict with secularized authority. Again, in England and America the free church form was molded in the unique environment of religious multiplicity which Puritan divisions produced. Consequently, it was as difficult for any religious group to respond to this environment in the classical sectarian pattern as for churchly institutions to maintain pretensions to uniformity—a fact which even church historians, impressed by Troeltsch's church-sect dichotomy, have been slow to recognize. And lastly, in both England and America the free church would seem to have been shaped by certain axioms of Puritan thought and piety. Indeed, this essay seeks to show that Puritanism both produced the problem and suggested the alternatives out of which the final free church concepts emerged.